The Role of Green Leadership in Green Human Resource Management Through Employee Green Behavior - Hani Haedatunnisa; Zakiyya Tunnufus; Ahmad Ahmad (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This discussion aims to examine the influence of Green Leadership on Green Human Resource Management by considering Employee Green Behavior as an intervening variable at the Lebak Regency Environmental Service. The approach used is quantitative through a survey method by distributingquestionnaires to 121 respondentsselectedusinga simple randomsampling technique . Data analysis was carried out using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the help of SmartPLS 3 to test the relationship betweenvariablessimultaneously. The results of the study indicate that GreenLeadershiphas a positive and significant effect on Employee Green Behavior and Green Human Resource Management . However, Employee Green Behavior doesnot have a significant effect on Green Human Resource Management . In addition, this variable is also unable to mediatethe relationshipbetweenGreen Leadership and Green Human Resource Management . This finding confirms that in public sector organizations, the role of leadership is more dominant in encouraging the implementation of environmental-based human resource management practices than through individual employee behavior